Triglyceride Microemulsion Systems with Palm Oil - Suhaimi, Hamdan; Kuang, Dzulkefly; Sharifudin, Salina; Che Rose, Laili (Universiti Putra Malaysia Press, 1996)
Microemulsions with refined, bleached and deodorized (RBD) and red palm oil (RPO), and solvents, stabilized by two oppositely charged ionic surfactants and a medium chain alcohol, were investigated. The results showed that only the solvent-in-oil microemulsions were prominent. The maximum solubilization of the both RBD and RPO were higher in the positively charged surfactant containing nitrogen atoms than in the negatively charged one. However, the results did not lend themselves to any decisive factor about the effect of solvents, length of hydrocarbon chain of the fatty acids or the presence of pigment on the microemulsion region in all systems investigated.